‘I was not prepared to go to Spain’. Work mobility of young people at the margins in Portugal - Clemente, M. (The Palgrave handbook of youth mobility and educational migration, 2021)
In the last few decades, a number of European policies and programmes have promoted learning, training and work mobility of young people across countries, inside and outside of Europe. Nevertheless, lower socio-economic and educational background continues to affect the mobility of young people from peripheral countries. In some cases, their experience of migration and work represents cases of ‘trafficking.’ This chapter takes an in-depth biographical look at trafficking via the story of a young man from the northern region of Portugal. Challenging the nature and causes as well as remedies for ‘trafficked’ migrants, the chapter argues politically and socially constructed categories such as ‘human trafficking’ fail to adequately capture the mobility as practised by the young male in the study. The chapter aims to contribute to a growing body of literature that questions categories such as ‘voluntary’ migrant and ‘trafficked’ migrant, based on simplistic, static and binary understandings of mobility and work experiences, constructed by law and public discourse. This study also suggests that, if migration is the only ‘chance’ for many young people with fewer opportunities and disadvantaged backgrounds, the mobility capacities of these young people should be strengthened to reduce their vulnerability to exploitation..